ANALISIS PENDAPATAN DAN STRATEGI PENGEMBANGAN USAHATANI JAGUNG HIBRIDA DI KECAMATAN LABUAN KABUPATEN DONGGALA” - Hasanudin Hasan; Alimudin Laapo; Rustam Abd Rauf (Universitas Tadulako, 2016)
This research aimed to analyze the income and the development strategy forhybrid cornfarming system at Labuan Sub District of Donggala Regency. The research used a purposive sampling method. Secondary and primary data were collected through observation, interview, questionnaire and focus group discussion (FGD). The income analysis indicated that the farmers’ income level of the hybrid corn farming system in Labuan sub district of Donggala regency was IDR 11,896,031.15/0.92/planting season/ha. The strategy for developing the hybrid corn farming system was strength-opportunity to supportprograms as follows : 1) improvingproduction by using or adopting newagriculture technologies; 2) establishing partnership with industry or government to obtain markets or production facility supplies; 3) increasing productivity through extension. Some factors needed to be taken into consideration in the development of the hybrid corn farming system in sub districtof Donggala regencyare the availability equipments, capital, post-harvest handling, fertilizer distribution, pest and diseaseprevention, climate change and the availability of youth labor. Both government and private sectors are needed to support the programs for developing the hybrid corn farming system in Labuan district of Donggala regencyin order to improve the welfare of the farmer groups and their family. Keywords: Development of Hybrid Corn, Farm, Income, Strategy.